Captain marvel (2019), volume 3 ebook - Thompson, Kelly (Captain Marvel (2019), 2020)
Collects Captain Marvel (2019) #12-17. Captain Marvel takes on the Avengers — to the death! Carol Danvers has fought alien hordes. Rescued the X-Men. Punched Thanos in the face. Literally saved the world! But now she faces her greatest challenge: kill her fellow Avengers! And she has 24 hours to do it! But why?! As the nightmare becomes reality and Earth's Mightiest Heroes begin to fall one by one, what does this mean for Carol — and for the world? When the mastermind behind Carol's deadly transformation is revealed, she must finally reconcile her human and alien sides — or lose them both. But as a plan begins to form, will the power of the Avengers be enough to save the world? It's a shocking new direction for Captain Marvel — and life on Earth will never be the same!